Polymer concrete to normal concrete bond strength: Mohr-Coulomb theory - Hussin, Mohd. Warid (Penerbit UTM Press, 2015)
This paper discusses an experimental study conducted to evaluate the bonding strength between polymer concrete (PC) and normal concrete (PC) bond substrate. Ground palm oil fuel ash (GPOFA) was incorporated as micro-filler in this polymer concrete (PC GPOFA) to investigate its effect on bonding strength. As comparisons, PC containing others filler were prepared, i.e., PC incorporating calcium carbonate (PC CaCO3), silica sand (PC Sand), and unground POFA (PC UPOFA) filler. Two tests were conducted to investigate the bonding between two substrates through slant shear and splitting tensile test. Since the critical condition surface (smooth surface) was provided, then, effect of bonding was determined by using Mohr-Coulomb theory. The overall results indicated that PC incorporating GPOFA was improved the bond to normal concrete. This result indicates that the bonding strength PC to NC at critical condition. This was affected by self-adhesive of polymer concrete to the normal concrete. The self-adhesive characteristic such as pure shear strength of polymer concrete to normal concrete also can be found in Mohr-coulomb analysis. All-in all, the PC incorporating ground POFA could improve the bond to the normal concrete. These findings expected to bring the knowledge and information to engineers and fabricators